Deep Learning-Based Training for Junior High School Teachers in Mempawah - Radiana, Usman; Rosnija, Eni; Afandi, Afandi; Waruwu, Marinu; Halida, Halida; Sadewo Wahyu Hartouo, Aji; Rudiansyah, Rudiansyah; Darmawan, Darmawan (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: The implementation of deep learning-based instruction not only offers a more adaptive and personalized approach to student needs, but also requires teacher readiness and increased competency to implement it effectively in the classroom. Therefore, the goal of this community service activity is to improve the professional competence of junior high school teachers in Mempawah. so that they are able to design and implement learning processes that are more meaningful, creative, and oriented towards developing students' high-level thinking skills. Contribution: This training provides a real contribution in improving teachers' professional competence while helping teachers understand the concepts, implementation strategies, and evaluation techniques of deep learning- based learning, so that they can be applied in teaching and learning activities. Method: This community service activity was implemented using a descriptive qualitative approach through lectures, discussions, and training. The material presented by lecturers and students included an introduction to the basic concepts of deep learning, their application in learning, and relevant implementation strategies. Results: The training results demonstrated improved teacher competency in implementing deep learning- based instruction. Eighty-five percent of participants were able to design meaningful learning activities. This indicates the training's positive impact on improving teachers' pedagogical skills. Conclusion: This training shows that teachers need systematic planning, the role of a facilitator in implementation, and authentic evaluation of the Solo Taxonomy.